DNA Topoisomerase 1α Promotes Transcriptional Silencing of Transposable Elements through DNA Methylation and Histone Lysine 9 Dimethylation in Arabidopsis - Dinh, Thanh Theresa (2014)
RNA-directed DNA methylation (RdDM) and histone H3K9 dimethylation (H3K9me2) are related transcriptional silencing mechanisms that target transposable elements (TEs) and repeats to maintain genome stability in plants. RdDM is mediated by small and long noncoding RNAs produced by the plant-specific RNA polymerases Pol IV and Pol V, respectively. Through a chemical genetics screen with a luciferase-based DNA methylation reporter, LUCL, we found that camptothecin, a compound with anti- cancer properties that targets DNA topoisomerase 1α (TOP1α) was able to de-repress LUCL by reducing its DNA methylation and H3K9me2 levels. Further studies with Arabidopsis top1α mutants showed that TOP1α silences endogenous RdDM loci by facilitating the production of Pol V-dependent long non-coding RNAs, AGONAUTE4 recruitment and H3K9me2 deposition at TEs and repeats. This study assigned a new role in epigenetic silencing to an enzyme that affects DNA topology.